A Permian nurse log and evidence for facilitation in high‐latitude Glossopteris forests. (7th May 2020) - Decombeix, Anne‐Laure; Durieux, Thibault; Harper, Carla J.; Serbet, Rudolph; Taylor, Edith L.
Abstract : The biology of trees that grew in high‐latitude forests during warmer geological periods is of major interest in understanding past and future ecosystem dynamics. As we study the different plants that composed these forests, it becomes possible to make comparisons with ecosystem processes that occur today. Here we describe a silicified late Permian (Lopingian) glossopterid (seed fern) trunk from Skaar Ridge, central Transantarctic Mountains, Antarctica, with evidence of glossopterid rootlets growing into its wood. The specimen is interpreted as a nurse log similar to those seen in some extant forests. Together with evidence of glossopterid roots growing within the lacunae of older roots, this new specimen suggests the existence of facilitative interactions among the glossopterid trees that dominated the high‐latitude forests of Gondwana during the late Permian. More generally, the existence of self‐facilitation might have favoured the expansion of glossopterids within various environments, especially those at high palaeolatitudes, during the Permian icehouse to greenhouse transition.